Population Structure and Genetic Diversity of Sheep Breeds in the Kyrgyzstan - Deniskova, Tatiana; Dotsev, Arsen; Lushihina, Eugenia; Shakhin, Alexey; Kunz, Elisabeth; Medugorac, Ivica; Reyer, Henry; Wimmers, Klaus; Khayatzadeh, Negar; Sölkner, Johann; Sermyagin, Alexander; Zhunushev, Asankadyr; et al. (Frontiers in Genetics, 2019)
Sheep are a main livestock species of Kyrgyzstan, a Central Asian country with predominating mountain terrain. The current gene pool of local sheep resources has been forming under diverse climate conditions from the era of the trading caravans of the Great Silk Road, through the Soviet period of large-scale livestock improvements, which was followed by the deep crisis at the end of the 20th century, up to now. However, not much is known about the genetic background and variability of the local sheep populations. Therefore, our aims were to provide a characterization of the population structure and genetic relations within the Kyrgyz sheep breeds and to study their genetic connections with the global sheep breeds using SNP analysis. Samples of the Alai (n=31), Gissar (n=30), Kyrgyz coarse wool (n=13), Aykol (n=31), and Tien-Shan (n=24) breeds were genotyped with the OvineSNP50 BeadChip or the Ovine Infinium HD BeadChip (Illumina Inc., USA). The measure of inbreeding based on runs of homozygosity showed a minimum value in the Aykol breed (FROH = 0.034), while the maximum was found in the Alai breed (FROH = 0.071). Short ROH segments (ROH≤4Mb) were predominant in all breeds. Long ROH segments (ROH>16Mb) were absent in the Gissar breed. The Gissar and Aykol breeds had the highest values of the effective population sizes estimated for five generations ago (Ne5=660 and 563), whereas the Alai and Kyrgyz coarse wool displayed lower values (Ne5 =176 and 128, respectively). The synthetic origin of the Aykol breed was clearly evidenced by all analyses applied. Based on the network and admixture analyses of the Kyrgyz and global sheep breeds, the Tien-Shan and the Russian semi-fine wool breeds demonstrated a common ancestry that most likely is due to a contribution of the Lincoln breed. The Gissar, Aykol and Kyrgyz coarse wool breeds showed a genetic background predominating in sheep populations from Iran and China whereas the Alai demonstrated the different ancestry type. The revealed admixture patterns probably resulted from the exchange and trade during the era of the Great Silk Road, which partly overlapped with historical and archeological findings.